Preclinical advantages of intramuscularly administered peptide A3-APO over existing therapies in Acinetobacter baumannii wound infections - Ostorhazi, Eszter (Oxford University Press, 2010)
OBJECTIVES: The designer antibacterial peptide A3-APO is efficacious in mouse models of Escherichia coli and Acinetobacter baumannii systemic infections. Here we compare the efficacy of the peptide with that of imipenem and colistin in A. baumannii wound infections after burn injury. METHODS: CD-1 mice were inflicted with burn wounds and different inocula of A. baumannii, isolated from an injured soldier, were placed into the wound sites. The antibiotics were given intramuscularly (im) one to five times. Available free peptide in the blood and the systemic toxicity of colistin and A3-APO were studied in healthy mice. RESULTS: While toxicity of colistin was observed at 25 mg/kg bolus drug administration, the lowest toxic dose of A3-APO was 75 mg/kg. In the A. baumannii blast injury models, 5 mg/kg A3-APO improved survival and reduced bacterial counts in the blood as well as in the wounds and improved wound appearance significantly better than any other antibiotic treatment. The free peptide concentration in the blood did not reach 1 µg/mL. CONCLUSIONS: Peptide A3-APO, with an intramuscular therapeutic index of 15, is more efficacious and less toxic than any existing burn injury infection therapy modality against multidrug-resistant Gram-negative pathogens. A3-APO administered by the im route probably binds to a biopolymer that promotes the peptide's biodistribution.